Peranan Tabungan Terhadap Kartu Atm Pada PT. Bank of India Indonesia Tbk - Christina Panjaitan (Jurnal Pajak dan Bisnis, 2021)
ATM is one of the bank services that can automatically serve customers in making transactions. ATMs play an important role in creating and encouraging customer interest in savings products with the aim that the amount of savings funds increases.This study aims to determine and analyze the extent of the effect of savings on ATM cards. The variables studied were seen from the amount of savings with the number of ATM cards and from data taken from 2015 to 2019. The data collection methods used interviews and literature study.The results of the study indicate that savings are very influential on ATM cards, because if you want to have an ATM card you have to open or have a savings account first. From this research it can be concluded that savings from time to time continue to increase, as well as ATM cards from time to time have also increased. Savings have a positive influence on ATM cards at PT. Bank of India Indonesia Tbk and have a mutually supporting relationship.